The Feeding Peculiarities of the Antarctic Seals in the Region of the Archipelago of Argentina Islands - Dykyy, I. (Український антарктичний журнал, 2009)
The detailed analysis of a food of the Antarctic species of seals around Argentine islands archipelago, that was spent through out 11 Ukrainian Antarctic expedition (2006-2007), has shown that krill (Euphausia superba) is the main type of food for the major species of seals in region. Krill makes 97,2 % to a diet of fur seals (Arctocephalus gazella) and 90 % to a diet crabeater seal (Lobodon carcinophagus) during the summer period. It is established rather big dimensional and weight rates to young growth in comparison with literary data àccording to Weddell seal (L. weddelli) newborns monitoring. It testifies to enough qualitative and sufficient forage reserve for pregnant Weddell seal females in archipelago water area in which diet krill prevails also (about 70 %). Considering that from 5 seals species counted within archipelago, the most numerous is the crabeater seal and a southern fur seal - these species can be used as «species indicators» of krill distribution and quantity in the given region. It is established, that the leopard seal's fodder diet is similar, to a diet of a specie around eastern Antarctic, despite an essential latitude difference of specie habitat arrangements. Проведений протягом 11-ї Української антарктичної експедиції (2006-2007 рр.) грунтовний аналіз живлення антарктичних видів тюленів у районі архіпелагу Аргентинські острови показав що у більшості видів тюленів регіону в раціоні переважає криль (Euphausia superba). Протягом літнього періоду криль складає 97,2% раціону морських котиків (Arctocephalus gazella) та 90% раціону крабоїда (Lobodon carcinophagus). Згідно з моніторингом новонароджених тюленя Уеддела (Leptonychotes weddelli) встановлено відносно великі розмірні та вагові показники молодняку в порівнянні з літературними даними, що свідчить про якісну й достатню кормову базу для вагітних самиць Уеддела в акваторії архіпелагу, в раціоні яких теж переважає криль (близько 70%). Враховуючи, що з п'яти видів облікованих у межах архіпелагу тюленів найбільш багаточисельними є тюлень-крабоїд та південний морський котик, ці види можуть бути використані як «види-індикатори» поширення та чисельності крилю при встановленні його запасів у даному регіоні. Встановлено, що кормовий раціон морського леопарда максимально подібний до раціону виду в районі Східної Антарктики, попри суттєву різницю широтного розташування біотопів виду.